Teachers' Views on Air Pollution and Personal Hygiene Promotion Strategies - Hidayatur Rokhmah; Yuli Kurniawati Sugiyo Pranoto; Ali Formen (Journal of Health Education, 2025)
Background: Children are vulnerable to air pollution, especially in their early life and so far there are no personal hygiene promotion strategies specifically aimed at addressing health threats or vulnerabilities in children in industrial areas. Therefore, the study aimed to determine teachers' views on air pollution and personal hygiene promotion strategies for children's health. Methods: This study used a quantitative method conducted with structured interviews. Respondents in this study were kindergarten teachers who taught in Ngaliyan District, totaling 95 teachers. The data analysis technique used was theme analysis technique. Results: Based on the interview results, teachers' views on air pollution are categorized as good. Respondents can mention sources of information about air pollution, causes of air pollution, the effect of air pollution on children's health, and diseases that arise due to air pollution. Teachers' views regarding personal hygiene promotion strategies are not good, especially in protecting children's health from air pollution. Conclusion: Teachers' views on air pollution are good but in personal hygiene promotion strategies, especially related to protecting children's health from exposure and the impact of air pollution, counseling, seminars, workshops, or similar activities are still rare. This study is expected to contribute to early childhood education, especially related to children's health.